Baby, You Can Drive My Car: Advertising Women's Freedom in 1920s America - Rabinovitch-Fox, Einav (American Journalism, 2016)
This article examines how understandings of women's new political and social status were constructed in car advertisements that appeared in Vogue during the post-suffrage age, and how the discourse presented in these ads was used to promote ideas regarding women's liberation while also delineating the limits of this freedom. Focusing on cars—a consumer product that was highly associated with mobility and modernity—the article illuminates how ideas of women's liberation were inherently connected to the material experience of consumption and the central role that advertising played in the legitimization and mainstreaming of feminist ideas. Car ads offered women a visual vocabulary to imagine their new social and political roles as citizens and to play an active role in shaping their identity as modern women.
Keywords: Business History and gender